Factors associated with overloading in the primary caregiver. Medellin, 2017 - Torres-Avendaño, Beatriz; Agudelo-Cifuentes, Maite Catalina; Pulgarin-Torres, Ángela María; Berbesi-Fernández, Dedsy Yajaira (Universidad y Salud, 2018)
Introduction: The increase in dependent people leads to the need for caregivers who assume basic tasks of care. The responsibility to care is assumed mainly by family members and the constant care impacts on changes of personal, family, labor and social nature. Objective: To identify the main sociodemographic and care factors associated with the overload in the primary caregiver in the city of Medellín during 2017. Materials and methods: A cross-sectional, quantitative study was made, which primary information source was obtained by telephone surveys. The sample was 340 caregivers and the consent was verbal. Results: 92.6% of the caregivers were women whose average age was 57; 53.8% perceived their health as regular or bad. The prevalence of overload was 39.7% and the associated characteristics were poor perception of health, abandonment of activities and not receiving pre-care training. Conclusions: The caregiver is a subject with rights that requires care in risk prevention programs that derive from care. It is necessary to provide education and accompaniment to caregivers so they are empowered of their health.